An Electrogenic Sodium Pump in Limulus Ventral Photoreceptor Cells - Brown, J. E. (The Rockefeller University Press, 1972)
A hyperpolarization can be recorded intracellularly following either a single bright light stimulus or the intracellular injection of Na(+). This after-hyperpolarization is abolished by bathing in 5 x 10(-6) M strophanthidin or removal of extracellular K(+). Both treatments also lead to a small, rapid depolarization of the dark-adapted cell. When either treatment is prolonged, light responses can still be elicited, although with repetitive stimuli the responses are slowly and progressively diminished in size. The rate of diminution is greater for higher values of [Ca(++)](out); with [Ca(++)](out) = 0.1 mM, there is almost no progressive diminution of repetitive responses produced by either K(+)-free seawater or strophanthidin. We propose that an electrogenic Na(+) pump contributes directly to dark-adapted membrane voltage and also generates the after-hyperpolarizations, but does not directly generate the receptor potential. Inhibition of this pump leads to intracellular accumulation of sodium ions, which in turn leads to an increase in intracellular Ca(++) (provided there is sufficient extracellular Ca(++)). This increase in intracellular calcium probably accounts for the progressive decrease in the size of the receptor potential seen when the pump is inhibited.